2019
DOI: 10.1002/adtp.201900018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Integrin α6‐Targeted Peptide for Nasopharyngeal Carcinoma‐Specific Nanotherapeutics

Abstract: Integrin α6 emerges as an attractive cancer therapeutic target. Here, the authors present for the first-time, that integrin α6 is overexpressed in nasopharyngeal carcinoma (NPC) and serves as a prognostic predictor and a cancer stem cell (CSC) biomarker. An NPC-targeted peptide CRWYDENAC (dubbed RWY) with high specificity and affinity for integrin α6 is identified, and an integrin α6-targeted nanotherapeutic against NPC is developed by encapsulating a cisplatin prodrug Pt(IV) with RWY-grafted polymeric nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
(89 reference statements)
0
26
0
Order By: Relevance
“…Here, we confirmed that integrin α6 was overexpressed in human PDAC (Figure 1A,B) and increased integrin α6 had poorer prognosis for PDAC patients (Figure 1C). Recently, a peptide CRWYDENAC (dubbed RWY) targeting integrin α6 has been identified 8 and employed for nanotherapeutics of nasopharyngeal carcinoma 8 and for PET imaging of hepatocellular carcinoma by our team 9 . Here, we used the Ala scanning mutagenesis to modify the RWY peptide.…”
Section: Figurementioning
confidence: 99%
“…Here, we confirmed that integrin α6 was overexpressed in human PDAC (Figure 1A,B) and increased integrin α6 had poorer prognosis for PDAC patients (Figure 1C). Recently, a peptide CRWYDENAC (dubbed RWY) targeting integrin α6 has been identified 8 and employed for nanotherapeutics of nasopharyngeal carcinoma 8 and for PET imaging of hepatocellular carcinoma by our team 9 . Here, we used the Ala scanning mutagenesis to modify the RWY peptide.…”
Section: Figurementioning
confidence: 99%
“…In our previous study, we screened out a peptide CRWYDDENAC (RWY) by phage display technology specific for nasopharyngeal carcinoma, and further identified that RWY was binding to integrin α6 which was highly expressed in multiple tumors. 25 Integrins, heterodimeric cell-face receptors composed of α and β subunits, are closely related to malignant biological behaviors in tumors including migration, invasion, metastasis and angiogenesis via mediating cell adhesion and signal transduction. [26][27][28][29] Integrin α6 subunit, encoded by ITGA6 gene in mammals, can be heterodimerized with either integrin β1 subunit or β4 subunit to form integrin α6β1 and α6β4, binding mostly and specifically to the extracellular matrix laminins.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment regime includes radiotherapy followed by cisplatin-loaded chemotherapy in case of advanced metastasis [12]. Surgery is generally avoided because of its sensitive area of occurrence [10,13]. However, the poor survival rate of nasopharyngeal carcinoma is an indication that there is a need to develop novel treatment therapies.…”
Section: Introductionmentioning
confidence: 99%